Variation in Amino Acid Contents of Pale Green and Purple Kohlrabis (Brassica oleracea var. gongylodes) - Hoon Kim, Haeng; Ju Bong, Sun; Abdullah Al-Dhabi, Naif; Valan Arasu, Mariadhas; Un Park, Sang (Asian Journal of Chemistry, 2015)
Vegetables from the brassicaceae family are among the most commonly grown vegetables worldwide. Kohlrabi contains health-promoting phytochemicals and has good levels of minerals. Here, we investigated amino acid contents variations in pale green and purple kohlrabis. Twenty-one different amino acids were found in varying proportions in pale green and purple kohlrabis. The levels of these amino acids varied widely between the pale green and purple kohlrabis. Purple kohlrabi contained higher amounts of 15 different amino acids, whereas pale green kohlrabi contained higher amounts of 6 different amino acids. Arginine was 3.2 times and histidine, tyrosine, leucine and aspartate were twice as high in purple kohlrabi than in pale green kohlrabi. Purple kohlrabi contained approximately 1.5 times more glutamate, threonine, cysteine, isoleucine and lysine compared with pale green kohlrabi. Considering the total amount, glutamine was the most dominating amino acid in both kohlrabis. The amount of glutamine was 1460.60 mg/100 g dry wt. in pale green kohlrabi types, which is 1.7 times the amount in purple kohlrabi. Alanine and norvaline were twice higher and methionine was 1.5 times higher in pale green kohlrabi than in purple kohlrabi. Our results show that both kohlrabis contain varying amounts of amino acids, suggesting that both kohlrabis are excellent, potential sources of amino acids in the development of food supplements.